English Teachers' Perception of ICT Use in EFL Teaching and Learning - Syamsuddin, Muhammad Rifqi; Fauzi, Rizki (PT ARRUS Intelektual Indonesia, 2025)
The integration of Information and Communication Technology (ICT) into English as a Foreign Language (EFL) classrooms is globally recognized as essential for enhancing teaching and learning processes. However, despite this acknowledged need, the specific application and perception of ICT use within Indonesian primary schools remain an under-researched area, representing a significant gap in the existing literature. This qualitative case study aimed to investigate Indonesian EFL teachers' perceptions of ICT utilization in their classrooms and to identify the critical factors influencing their decisions to adopt such technologies. Data were gathered through semi-structured interviews with two English teachers in a primary school located in Makassar, Indonesia. The principal findings indicate that the participating teachers held overwhelmingly positive attitudes toward ICT integration in their teaching practices. This favorable disposition was significantly shaped by several factors, including the perceived ease of use and the perceived usefulness of ICT tools, the teachers' underlying pedagogical beliefs, supportive school policies and curriculum mandates, the ready accessibility of technological resources, and the provision of professional development opportunities. Concurrently, the study identified notable challenges, such as student behavior related to technology misuse and the teachers' self-reported lack of sufficient ICT skills and confidence. A compelling observation from the findings is the coexistence of extensive ICT use and positive perceptions with a perceived lack of personal competence among teachers. This suggests that powerful external factors, such as institutional support and the clear utility of the technology, can be more influential in driving adoption than individual skill mastery or confidence in the initial stages. The implication is that confidence might develop as a consequence of sustained use, rather than being a prerequisite for it. This study offers valuable insights for practitioners and educational stakeholders committed to fostering effective ICT integration within EFL contexts, particularly in similar developing educational environments.